Chemical Sensors : Simulation and Modeling Volume 5: Electrochemical Sensors. - Korotchenkov, G. S. (Gennadiĭ Sergeevich) (Sensor technology series., 2013)
This is the fifth of a five-volume comprehensive reference work that provides computer simulation and modeling techniques in various fields of chemical sensing. The important applications for chemical sensing include such topics as bulk and surface diffusion, adsorption, surface reactions, sintering, conductivity, mass transport, and interphase interactions.